Labor of Love: Amateurs and Lay-expertise Legitimation in the Early U.S. Radio Field. (March 2018) - Croidieu, Grégoire; Kim, Phillip H.
Many actors claim to be experts of specialized knowledge, but for this expertise to be perceived as legitimate, other actors in the field must recognize them as authorities. Using an automated topic-model analysis of historical texts associated with the U.S. amateur radio operator movement between 1899 and 1927, we propose a process model for lay-expertise legitimation as an alternative to professionalization. While the professionalization account depends on specialized work, credentialing, and restrictive jurisdictional control by powerful field actors, our model emphasizes four mechanisms leading to lay-expert recognition: building an advanced collective competence, operating in an unrestricted public space, providing transformational social contributions, and expanding an original collective role identity. Our analysis shows how field expertise can be achieved outside of professional spaces by non-professionalized actors who master activities as a labor of love. Our work also reveals that lay-expertise recognition depends on the interplay between collective identities and collective competence among non-professional actors, and it addresses the shifting power dynamics when professional and non-professional actors coexist and strive for expertise recognition.